Treatment of Refractory Filamentary Keratitis With Autologous Serum Tears. Issue 5 (September 2017) - Read, Sarah P.; Rodriguez, Marianeli; Dubovy, Sander; Karp, Carol L.; Galor, Anat
Abstract : Purpose: To report a case of filamentary keratitis (FK) successfully treated with autologous serum tears and to review the pathogenesis and management of FK. Methods: Case report including high-resolution anterior segment optical coherence tomography and filament histopathology. Case Report: A 61-year-old Hispanic man presented with pain and photophobia of the right eye. He was found to have a corneal epithelial defect and a small peripheral infiltrate 4 months after Laser Assisted in situ Keratomileusis. After resolution of the epithelial defect, he developed FK. Over a 4-month period, conservative management with aggressive lubrication, lid hygiene, topical corticosteroids, topical cyclosporine, bandage contact lenses, and oral doxycycline failed to resolve the corneal filaments. Notably, treatment with 20% autologous serum tears, four times daily, led to a sustained resolution of the FK within 1 week. Conclusions: This case demonstrates the complexity of FK management and introduces autologous serum tears as a viable management option when conservative approaches to this condition fail.